Pengaruh Kepercayaan, Religiusitas dan Pendapatan Terhadap Minat Membayar Zakat Masyarakat Muslim Kota Pekanbaru - Andra Wahyudi; Nurizal Ismail (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study investigates the influence of trust, religiosity, and income on the interest in paying zakat among the Muslim community in Pekanbaru City. Trust in zakat institutions is defined as the belief that these institutions are professional, honest, and transparent in managing zakat funds. Religiosity is measured as the level of adherence to religious teachings, while income reflects the economic status of the respondents. The research adopts a quantitative approach using a questionnaire as the data collection instrument from 114 respondents. Data analysis is conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM), and the results indicate that trust, religiosity, and income significantly influence the community's interest in paying zakat. These findings contribute to understanding the motivating factors or barriers among the Muslim community in Pekanbaru City in fulfilling their zakat obligations. The study provides practical implications for zakat institutions to enhance their transparency and professionalism to build trust among the public. It also offers deeper insights into the factors influencing community interest in zakat within a specific socio-economic context.